Clinical profiles of cancer-associated thrombosis among newly diagnosed patient with solid cancer / Faiza Naimat ... [et al.] - Naimat, Faiza; Loganathan Fahrni, Mathumalar; Md Isa, Khairil Anuar; Thiagarajan, Muthukkumaran; Kwok, Wen Ng (Faculty of Medicine, 2025)
Introduction: Cancer-associated thrombosis (CAT) is a clinically significant complication that is linked to cancer patients. However, evidence regarding epidemiology of CAT and clinical characteristics in Malaysian cancer patients is very limited. The objective of this study is to investigate baseline characteristics of cancer patient with VTE and clinical profile of the VTE event. Methods: There were 462 cancer patients who were in anticoagulant recipient list from Radiology and Oncology Pharmacy Department, Hospital Kuala Lumpur between 2018 and 2021. A total of 208 patients met the inclusion and exclusion criteria of our study. We analysed retrospectively with respect to underlying diseases or predisposing factors. Results: Mean age of CAT patient was 50.51 years old and body mass index was normal (24.01kg/m ). Patients were mostly having good performance status (0-1). The prevalence rates of CAT were higher in breast, gynaecology and lung. About 63% of the cases experienced DVT, 27.3% had pulmonary embolism and 9.6% of the cases experienced both DVT and PE. Lower extremities DVT was prevalence (28.4%) and followed by upper extremities DVT. Slightly more than 50% of the cases developed VTE within 3 months of cancer diagnosis. Conclusion: The clinical profiles of CAT in our study were different with patients in the West. Nevertheless, risk factors for cancer-related thrombosis found in our study were much consistent with current literature from Asia. The findings in this study may gave an insight on the direction of management of CAT and improve thromboprophylaxis strategies among newly diagnosed cancer patient. 2